Predictive validity of current sarcopenia definitions (EWGSOP2, SDOC, and AWGS2) for clinical outcomes: A scoping review. Issue 1 (23rd December 2022) - Stuck, Anna K.; Basile, Giacomo; Freystaetter, Gregor; de Godoi Rezende Costa Molino, Caroline; Lang, Wei; Bischoff‐Ferrari, Heike A.
Abstract: Over the last 3 years new definitions of sarcopenia by the Sarcopenia Definition and Outcome Consortium (2020, SDOC), European Working Group on Sarcopenia in Older People (2019, EWGSOP2) and Asian Working Group on Sarcopenia (2019, AWGS2) have been proposed. The objective of this scoping review was to explore predictive validity of these current sarcopenia definitions for clinical outcomes. We followed the PRISMA checklist for scoping reviews. Based on a systematic search performed by two independent reviewers of databases (Pubmed and Embase) articles comparing predictive validity of two or more sarcopenia definitions on prospective clinical outcomes published since January 2019 (the year these definitions were introduced) were included. Data were extracted and results collated by clinical outcomes and by sarcopenia definitions, respectively. Of 4493 articles screened, 11 studies (mean age of participants 77.6 (SD 5.7) years and 50.0% female) comprising 82 validity tests were included. Overall, validity tests on the following categories of clinical outcomes were performed: fracture ( n = 40, assessed in one study), mortality ( n = 18), function ( n = 11), institutionalization ( n = 7), falls ( n = 4), and hospitalization ( n = 2). Thereby, EWGSOP2 was investigated in 15 validity tests (18.3%) on all categories of clinical outcomes, whereas SDOC was investigated in four validity tests (4.9%) in one study on fractures in men only, and none of the validity tests investigated predictive validity by the AWGS2. However, we were not able to pool the data using a meta‐analytic approach due to important methodological heterogeneity between the studies. We identified various definitions of clinical outcomes that were used to test predictive validity of sarcopenia definitions suggesting that an agreement on an operational definition of a clinical outcome is key to advance in the field of sarcopenia. Moreover, data on predictive validity using the sarcopenia definitions by the SDOC and AWGS2 are still scarce and lacking, respectively. In a next step, prospective studies including both women and men are needed to compare predictive validity of current sarcopenia definitions on defined key clinical outcomes.